Trains, Culture, and Mobility: Riding the Rails - Fraser, Benjamin; Spalding, Steven D. (Lexington Books, 2011)
Trains, Culture and Mobility: Riding the Rails goes beyond textual representations of rail travel to engage an impressive range of political, sociological and urban theory. Taken together, these essays highlight the complexity of the modern experience of train mobility, and its salient relation to a number of cultural discourses. Incorporating traditionally marginal areas of cultural production such as graffiti, museums, architecture or even plunging into the social experience of travel inside the traincar itself, each essay constitutes an attempt to work from the act of riding the train toward questions of much larger significance. Crisscrossing cultures from the New World and Old, from East and West, these essays share a common preoccupation with the way in which trains and railway networks have mapped and re-mapped the contours of both cities and states in the modern period. Bringing together individual and large-scale social practices, this volume traces out the cultural implications of “Riding the Rails.”